Evaluation of Serum Levels of Essential Trace Elements (Calcium, Zinc, Copper, Selenium, Vitamin D And K) in Patients with Osteoarthritis: Serum Level Analysis of Some Essential Trace Elements (African Journal of Biomedical Research, 2024)
Osteoarthritis (OA) is a degenerative joint disease that affects both the articular cartilage and the underlying subchondral bone over time. Joint pain and stiffness are the most prevalent symptoms. The aim of this study was to estimate the serum levels of some essential trace elements in subjects with osteoarthritis (OA). A total of 300 subjects comprising of 150 OA (test group) and 150 non-osteoarthritis (healthy control) subjects, between the ages of 51 to 90 years old were recruited for this study. The control subjects were healthy individuals recruited from different locations in Ondo state. Questionnaires were administered first to the control subjects before being recruited for this study. Atomic absorption spectrometer was used to measure the serum concentrations of calcium, copper, zinc and selenium, after proper digestion with acid, while Vitamin D and K were measured using High Performance Liquid Chromatography (HPLC) and spectrophotometer respectively. There was high prevalence of female (60.7%) OA subjects when compared with their male (39.3%) counterpart. The concentrations of calcium, selenium and Vit. D of OA subjects were significantly higher (p